Effects of Corneal Hydration on Brillouin Microscopy In Vivo - Shao, Peng (Invest Ophthalmol Vis Sci, 2018)
PURPOSE: To investigate how corneal hydration affects the Brillouin frequency of corneal stroma. METHODS: From a simple analytical model considering the volume fraction of water in corneal stroma, we derived the dependence of Brillouin frequency on hydration and hydration-induced corneal thickness variation. The Brillouin frequencies of fresh ex vivo porcine corneas were measured as their hydration was varied in dextran solution and water. Healthy volunteers (8 eyes) were scanned in vivo repeatedly over the course of 9 hours, and the diurnal variations of Brillouin frequency and central corneal thickness (CCT) were measured. RESULTS: The measured dependence of Brillouin frequency on hydration, both ex vivo and in vivo, agreed well with the theoretical prediction. The Brillouin frequencies of human corneas scanned immediately after waking were on average ∼25 MHz lower than their daytime average values. For stabilized corneas, the typical variation of Brillouin frequency was ± 7.2 MHz. With respect to CCT increase or swelling, the Brillouin frequency decreased with a slope of −1.06 MHz/μm in vivo. CONCLUSIONS: The ex vivo and in vivo data agree with our theoretical model and support that the effect of corneal hydration on Brillouin frequency comes predominantly from the dependence of the tissue compressibility on the water. Corneal hydration correlates negatively with the Brillouin frequency. During daytime activities, the influence of physiological hydration changes in human corneas is < ± 10 MHz. The sensitivity to hydration may potentially be useful in detecting abnormal hydration change in patients with endothelial disorders.